2009
DOI: 10.1161/hypertensionaha.108.123364
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adiposity and Physical Activity on Arterial Stiffness in Healthy Children

Abstract: Abstract-Childhood obesity is increasingly prevalent in the community and is related to adverse cardiovascular outcomes during adulthood. In this study of healthy children, we evaluated the influence of adiposity and physical activity on carotid-femoral pulse wave velocity (PWV), an index of arterial stiffness and a marker of cardiovascular risk in adults. In 573 community-based children (mean age: 10.1Ϯ0.3 years; 51% boys), we measured body mass index and waist circumference. Percentage body fat was quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
180
9
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(221 citation statements)
references
References 32 publications
23
180
9
9
Order By: Relevance
“…Indeed, the author's previous reports have provided supporting evidence that the development of hypertension is associated with higher PWV in the carotid arteries of children with highest odds. 31 Mean PWV was reported as 4.6 ± 0.5 m s À1 in Australian school-children having higher body fat, 32 which is on par with children with MS in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, the author's previous reports have provided supporting evidence that the development of hypertension is associated with higher PWV in the carotid arteries of children with highest odds. 31 Mean PWV was reported as 4.6 ± 0.5 m s À1 in Australian school-children having higher body fat, 32 which is on par with children with MS in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…In adults, a positive relationship between obesity and PWV has been described in cross-sectional studies, 22,23 and a reduction in PWV was observed after losing weight, 24 although these studies had not considered the impact of BP values at the same time. Controversial results exist in the childhood population 14,25,26 that may be partially explained by differences in patient populations (age, sex, and small sample size) and heterogeneity of the techniques used. In our study, the vascular phenotype assessment was performed in a large number of nonobese and obese subjects by the same operators with homogeneous methodology in only 1 center.…”
Section: Discussionmentioning
confidence: 99%
“…m The quality of the evidence from longitudinal studies was downgraded from "low" to "very low" because of serious risk of bias in 3 studies that diminished the level of confidence in the observed effects. n Includes 47 cross-sectional studies (Brage et al 2004a(Brage et al , 2004bGutin et al 2005b;Wennlof et al 2005;Andersen et al 2006;Ekelund et al 2006Ekelund et al , 2009Hurtig-Wennlof et al 2007;Quiros-Tejeira et al 2007;Rizzo et al 2007Rizzo et al , 2008Butte et al 2007b;Ruiz et al 2007;Leary et al 2008;Mark and Janssen 2008;Sardinha et al 2008;Sakuragi et al 2009;Schofield et al 2009;LeBlanc and Janssen 2010;Nguyen et al 2010;Owen et al 2010;Carson and Janssen 2011;Holman et al 2011;Moreira et al 2011;Colley et al 2012;Hay et al 2012;Hearst et al 2012;Henderson et al 2012;Jimenez-Pavon et al 2012, 2013b, 2013cMartinez-Gomez et al 2012;Mota et al 2012;Mendoza et al 2012;Barreira et al 2013;Carson et al 2013;Chaput et al 2013;Janssen et al 2013;Lamotte et al 2013;Knowles et al 2013;…”
Section: Mpamentioning
confidence: 99%